Effectiveness of Baby Friendly Community Initiative (BFCI) on complementary feeding in Koibatek, Kenya: a randomized control study - Mildred Maingi; Judith Kimiywe; Sharon Iron-Segev (BMC, 2018)
Abstract Background Appropriate infant and young child nutrition is critical for proper growth and development. In order to promote optimal nutrition at an early age, the World Health Organization (WHO) and UNICEF have developed the Baby Friendly Hospital Initiative (BFHI) to address poor breastfeeding practices in maternity wards. However, impact is limited in less developed countries like Kenya, where more than half of all births are home deliveries. Therefore, Kenya has explored the adoption of Baby Friendly Community Initiative (BFCI) in its rural settings. In contrast to the BFHI, the BFCI supports breastfeeding and optimal infant feeding in community. BFCI has been implemented in Koibatek, in rural Kenya. This study aimed at assessing the effectiveness of BFCI on complementary feeding practices of children aged 6-23 months, by comparing intervention and control groups. Methods This was a randomized control study design that included 270 mother-infant pairs enrolled in the Baby Friendly Community Initiative (BFCI) project in Koibatek. Evaluation was carried out using structured questionnaires. Results A statistically significantly higher proportion of children in the intervention group compared to the control group attained minimum dietary diversity (77% vs. 58%; p = 0.001), minimum meal frequency (96% vs. 89%; p = 0.046) and minimum acceptable diet (77% vs. 61%; p = 0.005). The odds of attaining minimum dietary diversity, minimum meal frequency and minimum acceptable diet were statistically significantly higher for the intervention group compared to control group (OR: 4.95; 95%CI 2.44-10.03, p = < 0.001; OR: 14.84; 95%CI 2.75-79.9, p = 0.002; OR: 4.61; 95%CI 2.17-9.78, p = < 0.001 respectively). Conclusion The BFCI intervention was successful in improving complementary feeding practices. Strengthening and prioritizing BFCI interventions could have a significant impact on child health outcomes in rural Kenya. Trial registration ISRCTN03467700. Registration 24 September 2014. Retrospectively registered.